The study of the stability of the movement of the frontal working bodies of the combined aggregate for sowing seeds of re-crops, depending on the depth of tillage - Primkulov Bekzod; Boboniyozov Ergash; Khudayorov Mukhiddin (E3S Web of Conferences, 2023)
This article theoretically investigates the stability of the movement of frontal working bodies for strip tillage of an energy-saving combined aggregate for sowing seeds of re-crops, depending on the depth of tillage.At the same time, a differential equation was compiled that describes the change in the working depth of tillage by the frontal working bodies of the aggregate.Based on the equation, the dependences of the change in the amplitude of the depth of tillage by the section of the working bodies of the combined aggregate and the stiffness of the pressure spring were studied.